2018
DOI: 10.1155/2018/7940603
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anesthesia on the Immune System in Colorectal Cancer Patients

Abstract: Colorectal cancer (CRC) is the key leading cause of high morbidity and mortality worldwide. Surgical excision is the most effective treatment for CRC. However, stress caused by surgery response can destroy the body's immunity and increase the likelihood of cancer dissemination and metastasis. Anesthesia is an effective way to control the stress response, and recent basic and clinical research has shown that anesthesia and related drugs can directly or indirectly affect the immune system of colorectal cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 70 publications
0
25
0
1
Order By: Relevance
“…The mechanism may be that with prolonged operation time, the chance of external bacteria entering the cranium is increased, and the immune function of patients was inhibited under anesthesia. Dang, Y et al[20] claimed that anesthesia affected the number and activity of immune cells and the secretion of cytokines. Meninges and soft tissues are retracted for surgical exposure, resulting in reduced perfusion and time-dependent reduced local immunological defenses[21].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be that with prolonged operation time, the chance of external bacteria entering the cranium is increased, and the immune function of patients was inhibited under anesthesia. Dang, Y et al[20] claimed that anesthesia affected the number and activity of immune cells and the secretion of cytokines. Meninges and soft tissues are retracted for surgical exposure, resulting in reduced perfusion and time-dependent reduced local immunological defenses[21].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have long suggested that the choice of anesthetic agents may influence the immune system, in particular, that some anesthetic regimens may be associated with less immunosuppression. This is likely to be very important in cancer surgery [78] . With the enhanced recovery protocols now being used in cancer surgery there is an opportunity to move towards standardized anesthetic and perioperative care protocols that are known to reduce the magnitude of the postoperative systemic inflammatory response and therefore reduce the relative postoperative immunosuppression, with the aim of reducing postoperative morbidity, and disease recurrence in the context of cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yangjie Dang et al, [14] showed that compared to general anesthesia, regional anesthesia reduce the inhibition of immune function. Also Alan David Kaye et al, [15] advised to use regional analgesia than general anesthesia to avoid immune suppression, as the immunosuppressive effects of regional anesthesia may be less than the immunosuppressive effects of general anesthesia.…”
Section: Discussionmentioning
confidence: 99%